Effects of a probiotic containing the spore-forming bacterium Bacillus subtilis on the productivity, egg quality, and hematological parameters in quails - Poberezhets, J. M.; Chudak, R. A.; Novgorodska, N. V.; Skoromna, O. I.; GlavatchukV. А.; Farionik, T. V.; Kolechko, A. V. (Regulatory Mechanisms in Biosystems, 2025)
Introduction of probiotics to poultry feeding practices significantly reduces the risk of infections of the gastrointestinal tract, thus preventing the potential emergence of antibiotic resistance. To conduct the experiment, we selected Japanese quails aged 45 days. Two groups were formed, consisting of 20 individuals each, according to the analogue principle. The intake of the probiotic feed supplement by the experimental-group quails led to notable improvements in an array of parameters, compared with the control. Thus, it produced increases of 15.8% in the total yield of eggs, 15.6% in the laying capacity per one average laying quail, and 10.3% in the laying intensity. The parameters of eggs were also enhanced: we noted a 15.0% increase in the mass of eggs, a 9.8% increase in the mass of egg shell, a 21.0% increase in the yolk mass, a 12.1% increase in the albumen mass, and a 10.7% increase in the yolk/egg mass ratio. The egg width, egg height, egg volume were higher by 11.4%, 7.6%, and 7.0%, respectively. The probiotic promoted rises in the albumen parameters: 20.0% in height of albumen, 9.2% in lesser diameter, and 8.3% in larger diameter. At the same time, the increases in yolk measured 20.4% in height, 10.0% in lesser diameter, 13.1% in larger diameter, and 7.8% in the yolk index. Moreover, the quails that received the probiotic consumed 12.8% less fodder per 10 eggs than the control. The mass parameters were also observed to have been elevated. Thus, we observed increases of 7.5% in live mass, 38.8% in mean daily mass gain, and 37.8% in absolute mass. Accordingly, we registered a 8.5% greater pre-slaughter live mass, a 13.0% higher mass of non-eviscerated carcass, a 7.8% greater mass of semi-eviscerated carcass, a 12.0% heavier eviscerated carcass, and a 25.6% larger mass of the thoracic muscles. Furthermore, the experimental-group quails had improved blood par a meters, in particular increases in the hemoglobin level by 7.2%, erythrocytes by 24.7%, total protein by 16.1%, albumin by 13.5%, globulins by 18.5%, glucose by 13.8%, and calcium by 21.8%. Thus, the intake of the probiotic containing B. subtilis increased the productivity, stimulated the immunity, and enhanced metabolism in the quails, allowing obtaining high-quality and safe egg products.